1987
DOI: 10.1016/0008-8846(87)90011-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for determining bond strength development between cement paste and steel

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Prior investigations have shown that the cement-shale bond is affected by both cement and shale. Cement shrinkage and growth of the calcium hydroxide crystals at the interfacial zone of cement-bonded surfaces are well-known reasons to weaken cement bond with most interfaces including the cement-shale interface (Nakayama and Beaudoin, 1987;Mehta and Monteiro, 2013). Moreover, the swelling coefficient of the shale formation has a significant impact on interfacial bond between the cement and shale.…”
Section: Fig 1 Schematic Representation Of Zonal Isolation and Potementioning
confidence: 99%
See 1 more Smart Citation
“…Prior investigations have shown that the cement-shale bond is affected by both cement and shale. Cement shrinkage and growth of the calcium hydroxide crystals at the interfacial zone of cement-bonded surfaces are well-known reasons to weaken cement bond with most interfaces including the cement-shale interface (Nakayama and Beaudoin, 1987;Mehta and Monteiro, 2013). Moreover, the swelling coefficient of the shale formation has a significant impact on interfacial bond between the cement and shale.…”
Section: Fig 1 Schematic Representation Of Zonal Isolation and Potementioning
confidence: 99%
“…1 (Celia et al, 2005), the steel-cement and rock-cement interfaces are two of the most critical leakage pathways (Carey et al, 2007). While considerable attention has been given to the steel-cement interface (Baldan, 2004;Nakayama and Beaudoin, 1987;Zhai et al, 2006), little effort has been focused on studying the rock-cement interface. This article focuses on repair of the rock-, specifically shale, cement interface for seal integrity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the technology also has outstanding advantages such as simple construction, strong engineering adaptability, and signi cant saving of engineering materials (Cheng 2005). Anchor and shotcrete support technology has become one of the most economical and effective support methods applied in underground engineering (Nakayama 1987;Kang 2021).…”
Section: Introductionmentioning
confidence: 99%